A surface ion layer reaction method based on deep processing of household appliance color crystal

By using the surface ion layer reaction method on household appliance color crystal glass, composite UV varnish and curing it with ultraviolet light, the problem of poor waterproof performance of existing UV varnish is solved, and a coating with high brightness, stain resistance and wear resistance is achieved, which improves production efficiency and reduces costs.

CN119143405BActive Publication Date: 2025-03-14LONGKOU KENUOER GLASS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411595905.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-14
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing UV varnish has poor waterproof performance in daily use, which is prone to leave oil stains, fingerprints or stains, reducing the brightness of the coating. At the same time, the production process of the glass industry is single and the production efficiency is not high.

Method used

The surface ion layer reaction method based on deep processing of color crystals in household appliances is adopted. By carrying out back cover protection, cleaning, plasma treatment, coating surfactant and composite UV varnish, and curing under ultraviolet light, forming a highly wear-resistant and stain-resistant coating.

Benefits of technology

It realizes the high-gloss reflective effect like electroplated glass, improves the stain resistance and wear resistance of the coating, reduces production costs and time, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a surface ion layer reaction method based on deep processing of household appliance colored crystals, belongs to the technical field of colored crystal glass preparation, and comprises the following steps in sequence: performing bottom sealing protection on the tin surface of tempered glass; cleaning the air surface of the tempered glass, performing plasma treatment, coating a surfactant solution, rinsing with deionized water, coating a composite UV varnish, and finally obtaining a finished product after ultraviolet curing; wherein the composite UV varnish comprises acrylate varnish, epoxy acrylate, octaglycidyloxypropyl caged polysilsesquioxane, modified caged polysilsesquioxane monomer and photoinitiator; the modified caged polysilsesquioxane monomer is PDMS-modified glycidyloxypropyl caged polysilsesquioxane; the invention improves the stain resistance and wear resistance of the coating while maintaining the brightness of the coating through component adjustment on the basis of the existing UV varnish.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of colored crystal glass preparation, and in particular to a surface ion layer reaction method based on deep processing of household appliance colored crystal. Background Art

[0002] Colored crystal glass is a new type of decorative material, which is made by printing a layer of colored coating with ink or ink colored transparent coating on the surface of the glass, and then applying a bottom protective layer; as people's requirements for the quality and appearance of glass materials are getting higher and higher, colored crystal glass as a high-quality and high-appearance decorative glass material is being continuously improved and innovated.

[0003] UV varnish is a highly efficient and environmentally friendly ink that can dry quickly under ultraviolet light and has a good film-forming effect, which is conducive to improving printing speed and quality. It is widely used in the gloss processing of colored crystal glass to give decorations better visual effects, increase visual highlights, and improve appearance quality. Existing UV varnishes are mostly acrylic resins, which have high transparency, good gloss and wear resistance, but poor waterproof performance. It is very easy to leave oil stains, fingerprints or stains in daily use, reducing the brightness of the coating. On the other hand, the glass industry is constantly developing today, and the glass coating production process is basically finalized on screen printing, with few subsequent changes, a single process form, and low production efficiency. Summary of the invention

[0004] In view of the above problems, the present invention provides a surface ion layer reaction method based on deep processing of household appliance colored crystals.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0007] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer can be coated with a wear-resistant protective primer ink, which can be hardened after baking to form a protective layer;

[0008] (2) Cleaning the air surface of the tempered glass;

[0009] (3) Plasma treatment is performed on the air surface of the tempered glass, generally using a plasma treatment device to activate the surface;

[0010] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface;

[0011] (5) flushing the air surface of the tempered glass with deionized water;

[0012] (6) coating the air surface of the tempered glass with composite UV varnish, and curing the glass with ultraviolet light to obtain a finished product;

[0013] The composite UV varnish comprises acrylate varnish, epoxy acrylate, octa-glycidyloxypropyl caged polysilsesquioxane, modified caged polysilsesquioxane monomer and photoinitiator;

[0014] The preparation method of the modified cage-like polysilsesquioxane monomer comprises the following steps:

[0015] Octaglycidyloxypropyl caged polysilsesquioxane and monoamino-terminated polydimethylsiloxane are weighed and dissolved in a dioxane solvent, the temperature is raised to 90-100° C. and the mixture is stirred and refluxed for 1-2 hours. The mixture is cooled to room temperature and then poured into an acetonitrile solvent. The mixture is stirred thoroughly and allowed to stand to remove precipitation. The solvent is evaporated under reduced pressure to obtain the modified caged polysilsesquioxane monomer.

[0016] In some preferred embodiments, the tempered glass in step (2) is cleaned using a degreasing agent, such as a degreasing agent having a concentration of 20%.

[0017] In some preferred embodiments, the surfactant in step (3) is an anionic surfactant or a nonionic surfactant.

[0018] In some preferred embodiments, the coating thickness of the composite UV varnish in step (6) is 80-500 nm.

[0019] In some preferred embodiments, the coating method of the composite UV varnish in step (6) comprises the following steps:

[0020] Octaglycidyloxypropyl caged polysilsesquioxane is weighed and dissolved in diethyl carbonate to obtain solution A; the modified caged polysilsesquioxane monomer is weighed and dissolved in a mixed solvent of dioxane and acetonitrile to obtain solution B; the solution A and the solution B are mixed, and then the diethyl carbonate solution of the photoinitiator, the acrylate varnish and the epoxy acrylate are added, and the mixture is fully stirred and sprayed on the air surface of the tempered glass.

[0021] In some preferred embodiments, the composite UV varnish includes, by weight, 100 parts of acrylate varnish, 1-7 parts of epoxy acrylate, 6-10 parts of octaglycidyloxypropyl caged polysilsesquioxane, 6-10 parts of modified caged polysilsesquioxane monomer, and 0.1-0.2 parts of photoinitiator.

[0022] In some preferred embodiments, the epoxy acrylate is bisphenol A epoxy acrylate and / or aliphatic epoxy acrylate.

[0023] In some preferred embodiments, in the method for preparing the modified caged polysilsesquioxane monomer, the number average molecular weight of the monoamino-terminated polydimethylsiloxane is 1000-5000, and the mass ratio of the octaglycidyloxypropyl caged polysilsesquioxane to the monoamino-terminated polydimethylsiloxane is 10:(0.5-1.5).

[0024] In some preferred embodiments, the photoinitiator is triphenylsulfonium hexafluoroantimonate.

[0025] In some preferred embodiments, the wavelength of the ultraviolet light is 270-400 nm, and the light curing time is 1-200 s.

[0026] The beneficial effects of the present invention are:

[0027] (1) The present invention can produce a "mirror" effect with high brightness and reflectiveness like electroplated glass through a simple and convenient spraying method. The present invention uses UV rapid curing and does not require a 20-meter baking furnace, which saves manufacturing time and a lot of space, greatly reduces production costs, and improves production efficiency;

[0028] (2) The present invention improves the stain resistance and wear resistance of the coating while maintaining the brightness of the coating by adjusting the components on the basis of the existing UV varnish. Specifically, the modified caged polysilsesquioxane monomer of the present invention is based on octa-glycidyloxypropyl caged polysilsesquioxane as a raw material, and a hydrophobic polydimethylsiloxane segment is introduced through the ring-opening reaction of the amino group to the epoxy group, and then the epoxy acrylate and the octa-glycidyloxypropyl caged polysilsesquioxane are subjected to ring-opening polymerization and cross-linking under the action of a photoinitiator, and an interpenetrating structure is formed in the acrylate resin polymer chain, so that the coating has good flexibility and wear resistance, and at the same time, the coating is endowed with good waterproof, anti-fouling and fingerprint resistance, and the brightness is improved. DETAILED DESCRIPTION

[0029] The present invention is further described in conjunction with the following examples.

[0030] Example 1

[0031] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0032] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer is coated with a wear-resistant protective primer ink, which is hardened after baking to form a protective layer;

[0033] (2) Cleaning the air surface of the tempered glass using a 20% concentration degreasing agent to clean the tempered glass;

[0034] (3) performing plasma treatment on the air surface of the tempered glass using a plasma treatment device to activate the surface;

[0035] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface, wherein the surfactant is a sodium dodecylbenzene sulfonate solution having a concentration of 1 wt %;

[0036] (5) flushing the air surface of the tempered glass with deionized water;

[0037] (6) coating a composite UV varnish on the air surface of the tempered glass, and obtaining a finished product after ultraviolet light curing, wherein the coating thickness of the composite UV varnish is 200 nm, the wavelength of the ultraviolet light is 274-400 nm, and the light curing time is 80 s;

[0038] Wherein, the composite UV varnish comprises, by weight, 100 parts of acrylate varnish, 4.2 parts of epoxy acrylate, 7.8 parts of octa-glycidyloxypropyl caged polysilsesquioxane, 6.9 parts of modified caged polysilsesquioxane monomer, and 0.14 parts of photoinitiator;

[0039] The product model of the acrylic varnish is UV7000 (Dongguan Dingyan New Material Technology Co., Ltd.);

[0040] The epoxy acrylate may be bisphenol A epoxy acrylate or aliphatic epoxy acrylate. In this embodiment, bisphenol A epoxy acrylate is used.

[0041] The preparation method of the modified cage-like polysilsesquioxane monomer comprises the following steps:

[0042] Weigh octa-glycidyloxypropyl caged polysilsesquioxane and monoamino-terminated polydimethylsiloxane and dissolve them in a dioxane solvent, heat to 95°C and stir and reflux for 1 hour, cool to room temperature and pour into an acetonitrile solvent, stir thoroughly and let stand to remove precipitation, and evaporate the solvent under reduced pressure to obtain the modified caged polysilsesquioxane monomer; the number average molecular weight of the monoamino-terminated polydimethylsiloxane is 2000, and the mass ratio of the octa-glycidyloxypropyl caged polysilsesquioxane to the monoamino-terminated polydimethylsiloxane is 10:0.95; the result formula of the modified caged polysilsesquioxane monomer is as follows:

[0043]

[0044] The photoinitiator is triphenylsulfonium hexafluoroantimonate;

[0045] The coating method of the composite UV varnish comprises the following steps:

[0046] Octaglycidyloxypropyl caged polysilsesquioxane is weighed and dissolved in diethyl carbonate to obtain solution A; the modified caged polysilsesquioxane monomer is weighed and dissolved in a mixed solvent of dioxane and acetonitrile to obtain solution B; the solution A and the solution B are mixed, and then the diethyl carbonate solution of the photoinitiator, the acrylate varnish and the epoxy acrylate are added, and the mixture is fully stirred and sprayed on the air surface of the tempered glass.

[0047] Comparative Example 1

[0048] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0049] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer is coated with a wear-resistant protective primer ink, which is hardened after baking to form a protective layer;

[0050] (2) Cleaning the air surface of the tempered glass using a 20% concentration degreasing agent to clean the tempered glass;

[0051] (3) performing plasma treatment on the air surface of the tempered glass using a plasma treatment device to activate the surface;

[0052] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface, wherein the surfactant is a sodium dodecylbenzene sulfonate solution having a concentration of 1 wt %;

[0053] (5) flushing the air surface of the tempered glass with deionized water;

[0054] (6) coating a composite UV varnish on the air surface of the tempered glass, and obtaining a finished product after ultraviolet light curing, wherein the coating thickness of the composite UV varnish is 200 nm, the wavelength of the ultraviolet light is 274-400 nm, and the light curing time is 80 s;

[0055] The composite UV varnish is the same as that in Example 1, except that the modified cage-like polysilsesquioxane monomer is not included.

[0056] Comparative Example 2

[0057] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0058] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer is coated with a wear-resistant protective primer ink, which is hardened after baking to form a protective layer;

[0059] (2) Cleaning the air surface of the tempered glass using a 20% concentration degreasing agent to clean the tempered glass;

[0060] (3) performing plasma treatment on the air surface of the tempered glass using a plasma treatment device to activate the surface;

[0061] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface, wherein the surfactant is a sodium dodecylbenzene sulfonate solution having a concentration of 1 wt %;

[0062] (5) flushing the air surface of the tempered glass with deionized water;

[0063] (6) coating a composite UV varnish on the air surface of the tempered glass, and obtaining a finished product after ultraviolet light curing, wherein the coating thickness of the composite UV varnish is 200 nm, the wavelength of the ultraviolet light is 274-400 nm, and the light curing time is 80 s;

[0064] The composite UV varnish is the same as that in Example 1, except that the epoxy acrylate is not included.

[0065] Comparative Example 3

[0066] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0067] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer is coated with a wear-resistant protective primer ink, which is hardened after baking to form a protective layer;

[0068] (2) Cleaning the air surface of the tempered glass using a 20% concentration degreasing agent to clean the tempered glass;

[0069] (3) performing plasma treatment on the air surface of the tempered glass using a plasma treatment device to activate the surface;

[0070] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface, wherein the surfactant is a sodium dodecylbenzene sulfonate solution having a concentration of 1 wt %;

[0071] (5) flushing the air surface of the tempered glass with deionized water;

[0072] (6) coating the air surface of the tempered glass with acrylic varnish, and curing the varnish with ultraviolet light to obtain a finished product, wherein the coating thickness of the acrylic varnish is 200 nm, the wavelength of the ultraviolet light is 274-400 nm, and the light curing time is 80 s;

[0073] The acrylic varnish is the same as that in Example 1.

[0074] Example 2

[0075] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0076] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer is coated with a wear-resistant protective primer ink, which is hardened after baking to form a protective layer;

[0077] (2) Cleaning the air surface of the tempered glass using a 20% concentration degreasing agent to clean the tempered glass;

[0078] (3) performing plasma treatment on the air surface of the tempered glass using a plasma treatment device to activate the surface;

[0079] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface, wherein the surfactant is a sodium dodecylbenzene sulfonate solution having a concentration of 1 wt %;

[0080] (5) flushing the air surface of the tempered glass with deionized water;

[0081] (6) coating a composite UV varnish on the air surface of the tempered glass, and obtaining a finished product after ultraviolet light curing, wherein the coating thickness of the composite UV varnish is 100 nm, the wavelength of the ultraviolet light is 274-400 nm, and the light curing time is 10 s;

[0082] Wherein, the composite UV varnish comprises, by weight, 100 parts of acrylate varnish, 2 parts of epoxy acrylate, 10 parts of octa-glycidyloxypropyl caged polysilsesquioxane, 6 parts of modified caged polysilsesquioxane monomer, and 0.2 parts of photoinitiator;

[0083] The product model of the acrylic varnish is UV7000 (Dongguan Dingyan New Material Technology Co., Ltd.);

[0084] The epoxy acrylate is bisphenol A epoxy acrylate;

[0085] The preparation method of the modified cage-like polysilsesquioxane monomer comprises the following steps:

[0086] Weigh octa-glycidyloxypropyl caged polysilsesquioxane and monoamino-terminated polydimethylsiloxane and dissolve them in a dioxane solvent, heat to 90°C and stir and reflux for 2 hours, cool to room temperature and pour into an acetonitrile solvent, stir thoroughly and let stand to remove precipitation, and evaporate the solvent under reduced pressure to obtain the modified caged polysilsesquioxane monomer; the number average molecular weight of the monoamino-terminated polydimethylsiloxane is 1000, and the mass ratio of the octa-glycidyloxypropyl caged polysilsesquioxane to the monoamino-terminated polydimethylsiloxane is 10:0.5;

[0087] The photoinitiator is triphenylsulfonium hexafluoroantimonate;

[0088] The coating method of the composite UV varnish comprises the following steps:

[0089] Octaglycidyloxypropyl caged polysilsesquioxane is weighed and dissolved in diethyl carbonate to obtain solution A; the modified caged polysilsesquioxane monomer is weighed and dissolved in a mixed solvent of dioxane and acetonitrile to obtain solution B; the solution A and the solution B are mixed, and then the diethyl carbonate solution of the photoinitiator, the acrylate varnish and the epoxy acrylate are added, and the mixture is fully stirred and sprayed on the air surface of the tempered glass.

[0090] Example 3

[0091] A surface ion layer reaction method based on deep processing of household appliance colored crystals comprises the following steps in sequence:

[0092] (1) The tin surface of the tempered glass is sealed with a bottom layer for protection. The sealing layer is coated with a wear-resistant protective primer ink, which is hardened after baking to form a protective layer;

[0093] (2) Cleaning the air surface of the tempered glass using a 20% concentration degreasing agent to clean the tempered glass;

[0094] (3) performing plasma treatment on the air surface of the tempered glass using a plasma treatment device to activate the surface;

[0095] (4) coating the air surface of the tempered glass with a surfactant solution to change the surface tension and further activate the surface, wherein the surfactant is a nonylphenol polyoxyethylene ether solution having a concentration of 1 wt %;

[0096] (5) flushing the air surface of the tempered glass with deionized water;

[0097] (6) coating the air surface of the tempered glass with composite UV varnish, and curing the composite UV varnish with ultraviolet light to obtain a finished product, wherein the coating thickness of the composite UV varnish is 500 nm, the wavelength of the ultraviolet light is 274-400 nm, and the light curing time is 200 s;

[0098] Wherein, the composite UV varnish comprises, by weight, 100 parts of acrylate varnish, 7 parts of epoxy acrylate, 6 parts of octa-glycidyloxypropyl caged polysilsesquioxane, 10 parts of modified caged polysilsesquioxane monomer, and 0.1 parts of photoinitiator;

[0099] The product model of the acrylic varnish is UV7000 (Dongguan Dingyan New Material Technology Co., Ltd.);

[0100] The epoxy acrylate is aliphatic epoxy acrylate HD-2290;

[0101] The preparation method of the modified cage-like polysilsesquioxane monomer comprises the following steps:

[0102] Weigh octa-glycidyloxypropyl caged polysilsesquioxane and monoamino-terminated polydimethylsiloxane and dissolve them in a dioxane solvent, heat to 100° C., keep stirring and reflux for 1 hour, cool to room temperature and pour into an acetonitrile solvent, stir thoroughly and let stand to remove precipitation, and evaporate the solvent under reduced pressure to obtain the modified caged polysilsesquioxane monomer; the number average molecular weight of the monoamino-terminated polydimethylsiloxane is 5000, and the mass ratio of the octa-glycidyloxypropyl caged polysilsesquioxane to the monoamino-terminated polydimethylsiloxane is 10:1.5;

[0103] The photoinitiator is triphenylsulfonium hexafluoroantimonate;

[0104] The coating method of the composite UV varnish comprises the following steps:

[0105] Octaglycidyloxypropyl caged polysilsesquioxane is weighed and dissolved in diethyl carbonate to obtain solution A; the modified caged polysilsesquioxane monomer is weighed and dissolved in a mixed solvent of dioxane and acetonitrile to obtain solution B; the solution A and the solution B are mixed, and then the diethyl carbonate solution of the photoinitiator, the acrylate varnish and the epoxy acrylate are added, and the mixture is fully stirred and sprayed on the air surface of the tempered glass.

[0106] Experimental example

[0107] The wear resistance and antifouling properties of the UV varnish prepared in Examples 1-3 and Comparative Examples 1-3 were measured, wherein the test of coating hardness was based on GB / T26704-2011, the test of flexibility was based on GB / T1731-1993, the wear resistance was expressed as the wear per unit area per unit time under the conditions of a load of 750 g and a rotation speed of 500 r, the contact angle was observed and measured using an optical contact angle analyzer, the anti-fingerprint rate was the ratio of the fingerprint residue rate with and without coating, the fingerprint residue image was set to an upper threshold of 180 and a lower threshold of 120 by ImageJ, the area measurement function in ImageJ was used to measure the area of ​​white fingerprint residue and the overall fingerprint occupation area, and the fingerprint residue rate was obtained by ratio calculation, and the measurement results are as follows:

[0108]

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A surface ion layer reaction method based on deep processing of household appliance color crystal, characterized in that: The following steps are included in sequence: (1) Protect the tin surface of the tempered glass by sealing the bottom; (2) Cleaning the air surface of the tempered glass; (3) performing plasma treatment on the air surface of the tempered glass; (4) coating the air surface of the tempered glass with a surfactant solution; (5) flushing the air surface of the tempered glass with deionized water; (6) coating the air surface of the tempered glass with composite UV varnish, and curing the glass with ultraviolet light to obtain a finished product; Wherein, the composite UV varnish comprises, by weight, 100 parts of acrylate varnish, 1-7 parts of epoxy acrylate, 6-10 parts of octa-glycidyloxypropyl caged polysilsesquioxane, 6-10 parts of modified caged polysilsesquioxane monomer, and 0.1-0.2 parts of photoinitiator; The preparation method of the modified cage-like polysilsesquioxane monomer comprises the following steps: Octaglycidyloxypropyl caged polysilsesquioxane and monoamino-terminated polydimethylsiloxane are weighed and dissolved in a dioxane solvent, the temperature is raised to 90-100°C and the mixture is stirred and refluxed for 1-2 hours, the mixture is cooled to room temperature and then poured into an acetonitrile solvent, the mixture is stirred sufficiently and then allowed to stand to remove precipitation, and the solvent is evaporated under reduced pressure to obtain the modified caged polysilsesquioxane monomer; the number average molecular weight of the monoamino-terminated polydimethylsiloxane is 1000-5000, and the mass ratio of the octaglycidyloxypropyl caged polysilsesquioxane to the monoamino-terminated polydimethylsiloxane is 10:(0.5-1.5).

2. The surface ion layer reaction method based on deep processing of household appliance color crystal according to claim 1 is characterized in that: In step (2), the tempered glass is cleaned using a degreasing agent.

3. The surface ion layer reaction method based on deep processing of household appliance color crystal according to claim 1 is characterized in that: The surfactant in step (3) is an anionic surfactant or a non-ionic surfactant.

4. The surface ion layer reaction method based on deep processing of household appliance color crystal according to claim 1 is characterized in that: The coating thickness of the composite UV varnish in step (6) is 80-500nm.

5. The surface ion layer reaction method based on deep processing of household appliance color crystal according to claim 1 is characterized in that: The coating method of the composite UV varnish in step (6) comprises the following steps: Octaglycidyloxypropyl caged polysilsesquioxane is weighed and dissolved in diethyl carbonate to obtain solution A; the modified caged polysilsesquioxane monomer is weighed and dissolved in a mixed solvent of dioxane and acetonitrile to obtain solution B; the solution A and the solution B are mixed, and then the diethyl carbonate solution of the photoinitiator, the acrylate varnish and the epoxy acrylate are added, and the mixture is fully stirred and sprayed on the air surface of the tempered glass.

6. The surface ion layer reaction method based on deep processing of household appliance color crystal according to claim 1, characterized in that: The epoxy acrylate is bisphenol A epoxy acrylate and / or aliphatic epoxy acrylate.

7. The surface ion layer reaction method based on deep processing of household appliance colored crystals according to claim 1 is characterized in that: The photoinitiator is triphenylsulfonium hexafluoroantimonate.

8. The surface ion layer reaction method based on deep processing of household appliance colored crystals according to claim 1 is characterized in that: The wavelength of the ultraviolet light is 270-400 nm, and the light curing time is 1-200 s.

Citation Information

Patent Citations

  • Manufacturing method of anti-glare glass shell, anti-glare glass shell and electronic equipment

    CN111943519A

  • Resin composition, UV photocuring organic-inorganic hybrid coating and preparation method of UV photocuring organic-inorganic hybrid coating

    CN117757289A